Finite Element Analysis of The Effect of Fiber Content on The Flexural Strength of SFRC Beams with Steel Rebars - Ilham Nurhuda; Blinka Hernawan Prasetya; Nuroji Nuroji; Yulita Arni Priastiwi (Institute of Research and Community Outreach - Petra Christian University, 2024)
This research aimed at studying the effect of fiber content on the flexural strength and behavior of steel fiber reinforced concrete (SFRC) beams with steel rebars. The study employed finite element (FE) analysis to simulate the behavior of SFRC beams. The simulation results of the FE model were validated against experimental data. Subsequently, the validated model was utilized to analyze the strength and crack patterns of SFRC beams with steel rebars in comparison to conventional RC concrete beams without fibers. The parametric study indicates an average 9% increase in RC beam capacity for every 1% increment in fiber volume fraction. Moreover, this study reveals more substantial effects of steel fibers on beams with low reinforcement ratios. Crack analysis shows that cracks in the SFRC beams are distributed more evenly compared to plain RC beams at regions with the same bending moment, indicating enhanced strength to sustain loads, reduced deflection, and improved beam ductility.